CARA PELAPORAN LAPORAN ARUS KAS SEDERHANA UNTUK PELAKU USAHA - Hastuti, Rini Tri; Triyana; Fernando, Ferry (Jurnal Serina Abdimas, 2024)
Based on the results of the preliminary survey, we found that the students majoring in Social Sciences class 12 at SMAN 20 TANGERANG, that they only received basic accounting material for financial reports, limited to profit and loss reports, reports on changes in capital, and balance sheets. Therefore, they need to be equipped with additional knowledge about cash flow reports which are one component of financial reports. Based on the problems above, this PKM provides basic accounting training in reporting cash flow reports. This PKM provides material in the form of PPT to be discussed and presented during the training. Apart from the PPT as a reference material in the form of theory, several examples of cash flow reports and how to prepare them are also attached. PPT material will be distributed to students participating in the training before the training is carried out with the hope that participants will read it first to find out the material that will be discussed in the training. The purpose of preparing a cash flow report is to determine the realization of the company's cash receipts and expenditures so that the potential for cash realization in the future can be known. From this survey, we found training topics that suited partner needs. Next, at the implementation stage, we carry out training by preparing training materials in the form of modules which will be distributed during face-to-face training. The training lasted for one day. Finally, at the review stage, we will give quizzes and distribute questionnaires to students to determine their level of understanding of this topic. The output targets to be achieved for this training activity are: Obligatory output in the form of publication in the Serina journal and additional output in the form of HKI. ABSTRAK Berdasarkan hasil survei pendahuluan, kami menemukan pada siswa-siswi jurusan IPS kelas 12 SMAN 20 TANGERANG, bahwa mereka hanya mendapatkan materi akuntansi dasar untuk laporan keuangan sebatas laporan laba rugi, laporan perubahan modal, dan laporan neraca. Oleh sebab itu, mereka perlu dibekali tambahan pengetahuan tentang laporan arus kas yang merupakan satu kesatuan dari komponen laporan keuangan. Berdasarkan permasalahan di atas, PKM ini memberikan pelatihan akuntansi dasar pelaporan laporan arus kas. PKM ini memberikan materi berupa PPT untuk dibahas, dipresentasikan pada saat pelaksanaan pelatihan. Selain PPT sebagai acuan materi yang berupa teori, di lampirkan juga beberapa contoh laporan arus kas dan cara penyusunannya. Materi PPT akan di bagikan kepada siswa peserta pelatihan sebelum pelaksanaan pelatihan dengan harapan agar peserta membaca terlebih dahulu untuk mengetahui materi yang akan di bahas di pelatihan. Tujuan penyusunan laporan arus kas adalah untuk mengetahui realisasi penerimaan dan pengeluaran kas perusahaan sehingga dapat diketahui potensi realisasi kas di masa yang akan datang. Pada tahap perencanaan, kami datang ke mitra untuk melakukan survei pendahuluan dengan cara wawancara dengan guru-guru dan kepala sekolah. Dari survey ini, kami menemukan topik pelatihan yang cocok dengan kebutuhan mitra. Selanjutnya, pada tahap pelaksanaan, kami melakukan pelatihan dengan menyiapkan materi pelatihan dalam bentuk Modul yang akan dibagi pada saat tatap muka pelatihan. Pelaksanaan pelatihan berlangsung selama saru hari. Terakhir pada tahap review, kami akan memberikan kuis dan membagikan kuesioner kepada siswa-siswi untuk mengetahui tingkat pemahaman mereka atas topik ini. Target luaran yang akan dicapai atas kegiatan pelatihan ini adalah: Luaran wajib berupa publikasi pada jurnal Serina dan luaran tambahan berupa HKI.